Migrationُ s Developmental Role in Human Capital Formation: Evidence from (Morocco, India, and Jordan): Peran Migrasi dalam Pembentukan Modal Manusia: Bukti dari (Maroko, India, dan Yordania) - Shaymaa Rasheed Mohaisen; Ameera K. Lafta; Sohaila Abdul Zahra Mastour (Academia Open, 2026)
General Background: International migration has become a defining global phenomenon shaping economic and social structures in both sending and receiving countries. Specific Background: Migration is closely linked to human capital formation through remittances, knowledge transfer, and labor mobility, while simultaneously generating challenges related to skilled labor outflows. Knowledge Gap: Existing studies present divergent findings and lack comparative analysis across countries with different migration profiles. Aims: This study examines the developmental role of migration in human capital formation using comparative evidence from Morocco, India, and Jordan. Results: The findings reveal a dual relationship in which migration supports skill accumulation, educational financing, and professional networking, while also contributing to brain drain and sectoral skill shortages. Novelty: The article provides a cross-country analytical framework that highlights context-specific migration outcomes. Implications: The results underline the importance of integrated migration and development policies that leverage remittances, diaspora networks, and return migration to support sustainable human capital development. Keywords: International Migration, Human Capital, Remittances, Brain Drain, Development Key Findings Highlights: Migration generates both skill accumulation and skilled labor loss across countries Remittances serve as a strategic resource for education and economic stability National policy context determines developmental outcomes of migration